Privacy-Preserving Keyword Search With Access Control for Secret Sharing-Based Data Outsourcing - Ahmad Akmal Aminuddin Mohd Kamal; Masamune Okada; Masaya Fujisawa (IEEE Access)
Searchable encryption, also known as secure search, is a technology that enables search operations on encrypted data while maintaining confidentiality. Extensive research has been conducted on searchable encryption utilizing public key and symmetric encryptions. However, public key encryption incurs significant computational expenses and is inefficient for querying large databases, particularly in cloud settings. Hence, we focus on searchable encryption using a secret sharing scheme (also known as searchable secret sharing), which is recognized for its minimal computational complexity. A secret sharing scheme is a method for transforming secret inputs into several distinct values known as shares. Kamal et al. (2021) introduced a simple searchable encryption method utilizing secret sharing schemes, yet did not include user access control capabilities. In this study, we introduce a secure search method with user access control that employs secure computation based on a $(k,n)$ threshold secret sharing scheme, where every piece of data stored in the cloud has an owner, and owners grant access to users at their discretion. We assume a client-server model to perform secure computation between the owner, player, and $n≥ k$ cloud servers. Furthermore, we provide an in-depth analysis of the security aspects of our proposed distribution, query generation, and search processes, demonstrating that our approach is resilient to honest-but-curious adversaries with information from up to $k-1$ computing servers. Moreover, we include an improved and efficient method using an $(n,n)$ additive secret sharing scheme when assuming $n=k$ computing servers. We compare the proposed methods in terms of their computational and communication costs. Finally, we present a detailed performance analysis using Python, including a comparison with conventional secret sharing-based methods.